Implementation of Guidance and Counseling Management System in Regular Schools in Support of Inclusive Education: A Review of the Literature - Irhamna Romadlon; Uman Suherman; Ibrahim Al Hakim (International Journal Labs, 2025)
This study aims to examine various literature that discusses the implementation of guidance and counseling (BK) management systems in regular schools in the context of inclusive education. The research was conducted using the narrative literature review method on national sources indexed by SINTA and several relevant international articles. The results of the study show that the BK management system plays an important role in supporting the success of inclusive education, especially at the stage of planning, implementing, and evaluating services that are oriented to the individual needs of students. However, implementation in the field still faces obstacles, such as the limited competence of BK teachers in handling students with special needs (including slow learners), lack of coordination across professions, and lack of policy support from schools. This study recommends the need to strengthen the capacity of BK teachers, the development of school policies that favor diversity, and the use of technology in the BK management system.